Seasonal Variability of Historical and Projected Future Climate in the Kathmandu Valley - Lamichhane, Suraj; Basnet, Keshav; Baral, Nirmal Prasad; Katuwal, Tek Bahadur; Subedi, Upendra (Technical Journal, 2020)
Anthropogenic activities are the major drivers of climate change and the climatic variability is the major threat for the world development especially in Nepal. The Kathmandu Valley (KV) is the most urbanized capital city of Nepal that has sensed the climatic variation in terms of increase in temperature, precipitation, runoff, and flood for few decades. For the adaptation of climatic variability, historical and future climate change is depicted by the trend, seasonal, and yearly variation analysis using climate models based on observed data. Historically, minimum temperatures of the all seasons are in increasing and the seasonal average rate of precipitation in the KV watershed is declining. After analysis of the projected future climate using climate model (ACCESS-CSIRO-CCAM, CNRM-CM5 and CCSM4) with two representative concentration pathways (RCP) scenarios (i.e., RCP4.5 and RCP8.5), minimum and maximum temperature in the future (up to 2050) is increased by 0.66°C – 0.6°C in RCP 4.5 and 1.21°C –1.04°C in RCP8.5 scenario. The rise in temperature means the warmer day will be increased and the erratic behavior of the precipitation will be expected in the future and the basin is expected to be drier in dry season and wetter in wet season. The analysis provides the alternative information for the planner for better planning, management, and adaptation strategy.